The role of engagement in immigrant students' academic resilience. (December 2022) - Martin, Andrew J.; Burns, Emma C.; Collie, Rebecca J.; Cutmore, Matthew; MacLeod, Shona; Donlevy, Vicki
Abstract: Academic resilience refers to academic success despite chronic socio-educational adversity. Given increases in immigration across the world in the past decade (including in Europe), there have been calls to identify factors (e.g., engagement) that can better support immigrant students' academic resilience. With a sample of N = 17, 241 immigrant students from 18 European countries, the present investigation employed multi-level probit regression to determine the extent to which cognitive, behavioral, and social-emotional engagement predict academic resilience status at both the student- and school-level. Findings revealed that cognitive engagement and behavioral engagement, at both the student- and school-level, are positively associated with academic resilience (yielding moderate and large effect sizes), while the findings regarding social-emotional engagement were more equivocal. Highlights: Academic resilience is academic success despite socio-educational adversity. We sought to better support immigrant students' academic resilience. Multi-level probit regression focused on academic engagement as a support focus. Results revealed that cognitive and behavioral engagement were influential. Findings regarding social-emotional engagement were more equivocal.